Corporate social performance and corporate financial performance: the role of productivity and innovation in the moderated-mediation model - Yudhistira, Prillinaya; Winarno, Wahyu Agus; Kustono, Alwan Sri (Serbian Journal of Management, 2025)
This study aims to investigate the fundamental processes and particular circumstances that allow Corporate Social Performance (CSP) to impact Corporate Financial Performance (CFP). Based on the Instrumental Stakeholder Theory perspective, our research explains the mechanism of the relationship between CSP in improving CFP through the mediating role of Total Factor Productivity (TFP) with the main contingency factor, namely innovation. This study uses a panel data set of 133 firm-year observations of manufacturing firms listed on the Indonesia Stock Exchange (IDX) over the 2018–2021 period. This study proposes a new model that incorporates additional contextual variables in the form of innovation and uses a moderated mediation model for this study. Our results show that the relationship between Corporate Social Performance (CSP) and Corporate Financial Performance (CFP) is mediated by Total Factor Productivity (TFP), especially in small firms. In addition, this study also finds that the moderating effect of Research and Development (R&D) on the CSP-CFP relationship becomes apparent when applied to large firms. Small-sized companies in sectors, consumer cyclical and industrial, can enhance their CSR performance by integrating it into their corporate strategy, as strategic CSR can yield a competitive edge, boost productivity, and elicit a positive market response that improves financial performance. The implications of this study suggest that the company can enhance its CSR performance by integrating it into its corporate strategy. Strategic CSR has the potential to provide a competitive edge, boosting productivity and positively influencing financial performance through favorable market reactions.